APPLICATION OF LINEAR REGRESSION AND CORRELATION BETWEEN THE RESULTS OF SALES PROMOTION COSTS, USING PASCAL 5.0 - Didi Ruswandi; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2004)
One goal of data analysis is to estimate / calculate its effect quantitatively greater than the change of an event terjadap other events is by calculating regression and correlation coefficients using Pascal 5.0 programming. With this application, it can be known whether there is a relationship between cost of sales promotion with the results and the results can be predicted sales next year and the funds expended for the cost of more targeted and effective promotions.